Inescapable ecologies : a history of environment, disease, and knowledge - Nash, Linda Lorraine (ACLS Humanities E-Book., 2006)
Among the most far-reaching effects of the modern environmental movement was the widespread acknowledgment that human beings were inescapably part of a larger ecosystem. With this book, Linda Nash gives us a wholly original and much longer history of "ecological" ideas of the body as that history unfolded in California's Central Valley. Taking us from nineteenth-century fears of miasmas and faith in wilderness cures to the recent era of chemical pollution and cancer clusters, Nash charts how Americans have connected their diseases to race and place as well as dirt and germs. In this account, the rise of germ theory and the pushing aside of an earlier environmental approach to illness constituted not a clear triumph of modern biomedicine but rather a brief period of modern amnesia. As Nash shows us, place-based accounts of illness re-emerged in the postwar decades, galvanizing environmental protest against smog and toxic chemicals. Carefully researched and richly conceptual, Inescapable Ecology brings critically important insights to the histories of environment, culture, and public health, while offering a provocative commentary on the human relationship to the larger world.